Penerapan Model Problem Based Learning PBL Untuk Meningkatkan Hasil Belajar Materi Konsep, Jenis, Dan Fungsi Musik Kreasi Pada Peserta Didik Kelas XII IPA 4 SMAN 8 Denpasar - Gusti Ayu Made Puspawati; Gaudensia Ansari; Mirah Rahmawati (Student Research Journal, 2024)
This Classroom Action Research aims to improve the learning of the material "Understanding the Concepts, Types, and Functions of Creative Music" through the application of the Problem Based Learning (PBL) model. The research was conducted in two cycles in class XII Science 4 SMA N 8 Denpasar. Data collection methods involve observation, tests, and analysis of learners' learning outcomes. At the beginning of the study, observations showed that students faced difficulties in understanding the concepts, types, and functions of music creations. Therefore, this classroom action research is designed to integrate PBL as a primary learning approach. Each cycle consists of planning, execution, observation, and reflection. The results showed that the application of PBL significantly increased students' understanding of creative music material. In addition, interaction between students has also increased, illustrating the existence of collaboration in solving problems related to the concept of creative music. Post-test results show consistent improvement from cycle to cycle. This research can be concluded that, the PBL model is effective in increasing students' understanding of the concepts, types, and functions of music creation. The implications of this research can be used as a reference for the development of more innovative and problem-solving oriented learning strategies in the context of creative music art materials.